Causal interactions with an insular-cortical network in mild traumatic brain injury. Issue 157 (December 2022) - Li, Fengfang; Liu, Yin; Lu, Liyan; Li, Hui; Xing, Chunhua; Chen, Huiyou; Yuan, Fang; Yin, Xindao; Chen, Yu-Chen
Highlights: Acute mTBI can cause EC alterations mainly in the insula. Associations are found between abnormal EC and cognitive function in acute mTBI. Our study provides new insight into neuromechanism of cognitive impairment in mTBI. Abstract: Purpose: This study aimed to investigate the insula-based directional effective connectivity in mild traumatic brain injury (mTBI) using resting-state functional magnetic resonance imaging (fMRI) and to explore its relationship with cognitive performance. Methods: Sixty mTBI patients and 55 age-, gender- and years of education- matched healthy controls (HC) were recruited in this study. Using granger causality analysis (GCA), we selected bilateral insula as two individual seed regions to compare the difference of directional effective connectivity of insula between mTBI group and HC group, and analyze its relationship with cognitive performance. Results: Compared with HC, acute mTBI group showed decreased outflows from the left insula to the left middle frontal gyrus (MFG) and right rolandic operculum (Rol), increased inflow from the left supplementary motor area (SMA) to the left insula, decreased outflows from the right insula to the left superior frontal gyrus (SFG), as well as increased outflows from the right insula to the left superior temporal gyrus (STG). No significantly different inflows to the right insula from other regions were found. Correlation analyses revealed that the abnormal connectivity between insula and MFG, as well as insula and STG were associated with the cognitive function score. Conclusions: Our data demonstrated abnormalities in the effective connection pathways of insula in acute mTBI patients, while abnormal effective connectivity significantly correlated with cognitive function score. These findings may shed light on the pathophysiological mechanisms of cognitive impairment after mTBI.